2010
DOI: 10.1111/j.1523-1739.2009.01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Avifauna in Commercial Plantations

Abstract: The occurrence of fauna in commercial plantations is often associated with structural complexity. Through a meta-analysis, we tested whether the structural complexity of plantations could enhance bird species assemblages and whether bird assemblages respond differently depending on taxonomic affiliation, body size, and diet. Our analyses included 167 case studies in 31 countries in which bird assemblages in forests and plantations were compared and 42 case studies in 14 countries in which bird assemblages in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 23 publications
5
79
0
1
Order By: Relevance
“…The influence of the passive or active vegetation restoration after cropland abandonment in this region is consistent with the pattern of relationships between bird communities and the increase in structural complexity of growing vegetation that is observed worldwide (Wiens, 1989;Nájera and Simonetti, 2009). Nevertheless, this positive effect was considerable higher in pine plantations than in the secondary succession trajectory, and is mainly related to the ubiquitous presence of generalist woodland species in the plantations.…”
Section: Bird Species Richness and Regional Densitysupporting
confidence: 75%
“…The influence of the passive or active vegetation restoration after cropland abandonment in this region is consistent with the pattern of relationships between bird communities and the increase in structural complexity of growing vegetation that is observed worldwide (Wiens, 1989;Nájera and Simonetti, 2009). Nevertheless, this positive effect was considerable higher in pine plantations than in the secondary succession trajectory, and is mainly related to the ubiquitous presence of generalist woodland species in the plantations.…”
Section: Bird Species Richness and Regional Densitysupporting
confidence: 75%
“…doi:10.1016/j.foreco.2011.08.026 the contrary, other studies (Aratrakorn et al, 2006;Koh, 2008) have concluded that stand age did not influence species richness of groups like birds in oil palm landscapes. To date, survey efforts to investigate the impacts of management regimes have been limited to large plantation estates, whereas smallholdings have not been examined (Aratrakorn et al, 2006;Danielsen and Heegaard, 1995;Edwards et al, 2010;Koh, 2008;Peh et al, 2006;Najera and Simonetti, 2010a;Sheldon et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…are prone to burning in dry regions, which increases carbon emissions [17] and species within plantations differ in carbon sequestration rates [18]. Plantation species with open or structurally complex canopies can promote dense native understory regrowth and forest connectivity [19][20][21]. Conversely, fast-growing tree species with dense shade can function as "biological deserts" with very low biological diversity [22].…”
Section: Introductionmentioning
confidence: 99%